TINJAUAN METODE PENCEGAHAN KOROSI PADA SISTEM PERPIPAAN UTILITAS DI INDUSTRI KIMIA - Atdjeng Chrisnudin; Fadila Fitri Wulandari; Atsiil Putra Utama; Aulia Rahma Efendi; Aura Aldamah Dea; Tee Tze Kiong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Corrosion is a major problem in utility piping systems in the chemical industry, causing material damage, reduced operational efficiency, and safety risks. This study aims to review various commonly used corrosion prevention methods, including material selection, coating, cathodic protection, and control of operating conditions. The method used is a literature review of various scientific sources and industry standards. The results indicate that no single method is completely effective for all conditions, so a combination of methods tailored to the operating environment is necessary. An integrated approach has been proven to increase the service life of piping systems and reduce maintenance costs.